2017
DOI: 10.1002/lary.26897
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes and prognostic factors of sialendoscopy in salivary duct stenosis

Abstract: 4. Laryngoscope, 128:878-884, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 19 publications
2
30
0
Order By: Relevance
“…In this study, we present a prospective analysis of etiology‐specific responses to SASDS in patients with COSWS using the COSS questionnaire. Previous studies have shown that symptomatic response to SASDS varies in an etiology‐dependent manner, most likely reflecting different drivers of inflammation and obstruction in chronic sialadenitis . Although evidence for efficacy of SASDS in the treatment of sialolithiasis is robust, the limited power and generalizability of SASDS outcomes for COSWS can be attributed to predominantly retrospective design of most published studies, small sample sizes given the rare incidence of COSWS, short duration of postoperative follow‐up, and heterogeneous cohorts with an emphasis on sialolith‐based disorders.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this study, we present a prospective analysis of etiology‐specific responses to SASDS in patients with COSWS using the COSS questionnaire. Previous studies have shown that symptomatic response to SASDS varies in an etiology‐dependent manner, most likely reflecting different drivers of inflammation and obstruction in chronic sialadenitis . Although evidence for efficacy of SASDS in the treatment of sialolithiasis is robust, the limited power and generalizability of SASDS outcomes for COSWS can be attributed to predominantly retrospective design of most published studies, small sample sizes given the rare incidence of COSWS, short duration of postoperative follow‐up, and heterogeneous cohorts with an emphasis on sialolith‐based disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative localization of stenosis with ultrasound may help inform perioperative planning and help set expectations for treatment efficacy during patient discussions . Other studies show variable success rates for duct stenosis, with a substantial proportion having symptom persistence . Proximal and parenchymal stenoses are often not endoscopically accessible for the delivery of treatment given ductal branching and the limited maneuverability of the semirigid sialendoscopes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations